Alpha-1,2-mannosidase and hence N-glycosylation are required for regulatory T cell migration and allograft tolerance in mice. - Elaine T Long; Stephanie Baker; Vanessa Oliveira; Birgit Sawitzki; Kathryn J Wood (PLoS ONE, 2010)
Specific immunological unresponsiveness to alloantigens can be induced in vivo by treating mice with a donor alloantigen in combination with a non-depleting anti-CD4 antibody. This tolerance induction protocol enriches for alloantigen reactive regulatory T cells (Treg). We previously demonstrated that alpha-1,2-mannosidase, an enzyme involved in the synthesis and processing of N-linked glycoproteins, is highly expressed in tolerant mice, in both graft infiltrating leukocytes and peripheral blood lymphocytes.In this study we have identified that alpha-1,2-mannosidase expression increases in CD25(+)CD4(+) Treg when they encounter alloantigen in vivo. When alpha-1,2-mannosidase enzyme activity was blocked, Treg retained their capacity to suppress T cell proliferation in vitro but were unable to bind to physiologically relevant ligands in vitro. Further in vivo analysis demonstrated that blocking alpha-1,2-mannosidase in Treg resulted in the migration of significantly lower numbers to the peripheral lymph nodes in skin grafted mice following adoptive transfer, where they were less able to inhibit the proliferation of naïve T cells responding to donor alloantigen and hence unable prevent allograft rejection in vivo.Taken together, our results suggest that activation of alloantigen reactive Treg results in increased alpha-1,2-mannosidase expression and altered N-glycosylation of cell surface proteins. In our experimental system, altered N-glycosylation is not essential for intrinsic Treg suppressive capacity, but is essential in vivo as it facilitates Treg migration to sites where they can regulate immune priming. Migration of Treg is central to their role in regulating in vivo immune responses and may require specific changes in N-glycosylation upon antigen encounter.